Lexical Features in the Portuguese Translations of Contemporary Political Discourse: A Corpus-Based Analysis - Luo, Wenying; Zhang, Xiang (Forum for Linguistic Studies, 2025)
The characteristics of translations result not only from the interaction between linguistic systems but also from inherent elements of the translated text. This study emphasizes the empirical analysis of translation within the Sino-Portuguese translation context, specifically focusing on contemporary political discourse. The objective of this research is to examine the lexical features in the Portuguese translation of representative contemporary political texts through a comparable Sino-Portuguese corpus. The corpus comprises source texts in Chinese and their corresponding Portuguese translations, totaling 127,071 tokens in Chinese, 204,064 in Portuguese, and a reference corpus with original political texts (185,959 tokens). The comparative analysis revealed distinct lexical differences and translation strategies. A reduction in lexical richness was observed in the Portuguese translation compared to the original Chinese text, suggesting a post-translation simplification, alongside a higher lexical density in the Chinese version. The presence of connectors was more noticeable in the translation, adapting logical relations from Chinese. Nominalized structures prevailed in the Portuguese translation, while the Chinese version emphasized verbs. Chinese modal verbs were systematically replaced with diverse grammatical resources in the Portuguese translation, avoiding repetitions and conforming to the language’s conventions. Finally, translating institutional discourse necessitates a balance between semantic preservation and typological conformity, with implications for translator training and the analysis of transcultural discourses.